Female Journalists in the Digital Media Platform Environment - Wardatul Jannah (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
This research aims to explore the challenges faced by female journalists in the digital space, and to examine the safety threats they encounter, including online gender-based violence (OGBV), cyber trolling, and harassment. The study will also investigate the strategies employed by both female journalists and media organizations to address these issues. A mixed-methods approach will be used, qualitative methods. The qualitative data will be collected through in-depth document analysis of media safety protocols. The study will focus on digital space, which has not been extensively researched in terms of gender-based violence in journalism. By identifying the unique experiences and safety challenges faced by female journalists in this region, the research aims to contribute to a deeper understanding of the issue and provide recommendations for improving safety measures and gender-specific protection strategies. This research will offer valuable insights for media organizations globally in addressing the digital safety of female journalists and ensuring their well-being both online and offline.